Modified MWW molecular sieve as well as preparation method and application thereof
By modifying MWW molecular sieve, a catalyst with high activity, good selectivity and environmental protection was prepared, which solved the problems of low catalyst activity, poor selectivity and difficulty in recycling in the prior art, and was suitable for biomass dehydration and etherification reactions.
Patent Information
- Application Number
- CN202311370833.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, when using MWW molecular sieve in biomass catalytic reactions, the catalyst has low activity, poor selectivity, high toxicity and difficult to recover.
By modifying the MWW molecular sieve, a solid catalyst with suitable acid properties is prepared. The specific method includes acid eluting, adding thiol compounds, oxidation, and hydrothermal treatment.
The modified MWW molecular sieve catalyst exhibits the advantages of high activity, good selectivity, good environmental protection and easy recycling in biomass dehydration and etherification reactions.
Smart Images

Figure CN119858932A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of molecular sieves, and in particular to a modified MWW molecular sieve and a preparation method and application thereof. Background Art
[0002] The basic framework structure of crystalline microporous molecular sieves is based on a rigid three-dimensional TO4 (SiO4, AlO4, etc.) unit structure; in this structure, TO4 shares oxygen atoms in a tetrahedral manner, and the charge balance of the framework tetrahedron such as AlO4 is achieved through surface cations such as Na + , H + The existence of zeolite is maintained. It can be seen that the skeleton properties of zeolite can be changed by cation exchange. At the same time, there is a rich pore system with a certain pore size in the structure of zeolite. These pores are intertwined to form a three-dimensional network structure, and the skeleton can still exist stably after the water or organic matter in the pores is removed (US4439409). It is based on the above structure that molecular sieves not only have good catalytic activity and excellent shape selectivity for a variety of organic reactions, but also can achieve good selectivity through modification (US6162416, US4954325, US5362697).
[0003] The molecular sieve with MWW structure has two independent and unconnected ten-membered ring pore systems: one set of two-dimensional sinusoidal pores, the pore cross-section is approximately elliptical, and the pore size is 0.41nm×0.51nm, and the other set of ten-membered ring pores contains a cylindrical twelve-membered ring supercage with a size of 0.71nm×0.71nm×1.82nm, which is connected to the outside world through a slightly twisted ten-membered ring window (0.40nm×0.55nm). Its unique framework structure and acid properties, good thermal stability and hydrothermal stability make MWW molecular sieves important in traditional industrial catalysis. In recent years, biomass conversion and utilization technology has flourished. Compared with fossil resources, biomass resources have a higher oxygen content. If we want to use biomass resources to obtain the chemicals we use now, we must involve deoxygenation and dehydration reactions. 5-Hydroxymethylfurfural (HMF) is an important furan derivative, known as an important bridge connecting biomass chemical industry and petrochemical industry. Its synthesis has attracted extensive attention from researchers at home and abroad. 5-Ethoxymethylfurfural (EMF) is the product of HMF etherification. As a diesel additive, EMF can replace fuel. It has passed flight tests. The engine can run safely for several hours. It can significantly reduce the emission of smoke, sulfur oxides and nitrogen oxides in the exhaust gas and reduce pollution to the environment. Therefore, it is considered to be a very promising renewable green new fuel.
[0004] Acidic catalysts are commonly used catalysts for biomass dehydration or etherification reactions, including inorganic acids, inorganic salts and solid acids. Soluble inorganic acids are the cheapest acid catalysts, often catalyzing fructose dehydration in aqueous solutions, with high catalytic activity, but the generation of formic acid, levulinic acid and humin during the reaction is very serious. Solid acid has the advantages of no corrosion to equipment, little pollution and easy separation. CN103028424A reports a preparation method of a solid acid catalyst for the synthesis of 5-hydroxymethylfurfural, wherein the oxide is dissolved in deionized water, and the precipitation is completely precipitated with a precipitant, and after aging, the precipitate is washed, filtered and dried, and then the precipitate is immersed in a sulfuric acid solution or a chromium solution. After impregnation, the solid acid catalyst is roasted to obtain a solid acid catalyst for the synthesis of 5-hydroxymethylfurfural with a high yield. However, since the main active components of the catalyst are sulfate and chromium ions, it causes a certain burden on the environment.
[0005] The thin flaky crystal structure of MWW molecular sieves makes them have great potential in biomass catalytic conversion. In particular, CN104511271B discloses an MWW molecular sieve, SCM-1 molecular sieve. This molecular sieve has a two-dimensional layered structure and a huge external specific surface area of 185m 2 / g or more, exposing a large number of bowl-shaped twelve-membered ring semi-supercages on the outer surface of the crystal, making it potential for application in biomass macromolecular catalysis. However, when the molecular sieve is directly used in biomass dehydration or etherification reactions, due to its strong acid sites, it will cause a series of serious side reactions and has the disadvantages of low selectivity for the target product.
[0006] In summary, MWW molecular sieves have the potential for biomass catalysis, but there is currently no technology to apply MWW series molecular sieves to biomass catalytic reactions. This technical solution modifies MWW molecular sieves to obtain solid catalysts with suitable acid properties, so that they can be used in biomass dehydration or etherification reactions. And achieve the needs of improving the recovery rate of catalysts and green production. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems of low activity, poor selectivity, high toxicity and difficulty in recycling of biomass conversion catalysts in the prior art, and to provide a modified MWW molecular sieve and a preparation method and application thereof, which has the advantages of high activity, good selectivity, environmental protection and easy recycling.
[0008] In order to achieve the above objectives, the first aspect of the present invention provides a modified MWW molecular sieve having a schematic chemical composition as shown in the formula "mSiO2·nAl2O3·pSO3H", wherein 20≤m / n≤66, 25≤m / p≤150.
[0009] The second aspect of the present invention provides a method for preparing the modified MWW molecular sieve, which comprises: acid eluting the hydrogen-type MWW molecular sieve, adding a mercapto compound, oxidizing, and hydrothermally treating.
[0010] The third aspect of the present invention provides a use of the modified MWW molecular sieve as an adsorbent and / or a catalyst for conversion of organic compounds.
[0011] Through the above technical solution, the present invention has the following advantages:
[0012] The molecular sieve catalyst with the characteristics of the present invention is used for biomass dehydration and etherification reactions, which can effectively promote the diffusion of biomass macromolecules and reduce the formation of carbon deposits. Sugar macromolecules react on the active sites on the outer surface of the catalyst and quickly desorb without overreacting. That is, the molecular sieve of the present invention has the advantages of high activity, good selectivity, good environmental protection and easy recovery when used for biomass dehydration and etherification reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The XRD diagrams of the modified SCM-1 in Example 1 and the hydrogen SCM-1 in Comparative Example 1;
[0014] Figure 2 is the N2- adsorption-desorption curve of the modified SCM-1 in Example 1;
[0015] Figure 3 py-FTIR images of modified SCM-1 and hydrogen SCM-1 in Example 1;
[0016] Figure 4 The infrared images of -OH vibration peaks of hydrogen-type SCM-1 in Comparative Example 1 and hydrogen-type MCM-22 in Comparative Example 2;
[0017] Figure 5 (a) is a scanning electron microscope image (SEM) of the modified SCM-1 in Example 1;
[0018] Figure 5 (b) is a scanning electron microscope image (SEM) of the modified MCM-22 in Comparative Example 3. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The present invention provides a modified MWW molecular sieve having a schematic chemical composition as shown in the formula "mSiO2·nAl2O3·pSO3H", wherein 20≤m / n≤66, 25≤m / p≤150.
[0021] According to a preferred embodiment of the present invention, the schematic chemical composition of the modified MWW molecular sieve is 22≤m / n≤60, 26≤m / p≤130, preferably 25≤m / n≤55, 28≤m / p≤100.
[0022] According to a preferred embodiment of the present invention, the modified MWW molecular sieve The acid / Lewis acid ratio is 1.5-5.0, preferably 1.9-4.0.
[0023] According to a preferred embodiment of the present invention, the external specific surface area / total specific surface area of the modified MWW molecular sieve is 0.2-0.9, preferably 0.3-0.7.
[0024] According to a preferred embodiment of the present invention, the modified MWW molecular sieve has a nano-sheet morphology, and the crystal thickness is 5-15 nm, preferably 5-12 nm.
[0025] According to a preferred embodiment of the present invention, the MWW molecular sieve is SCM-1 molecular sieve and / or MCM-22 molecular sieve, preferably SCM-1 molecular sieve.
[0026] The invention provides a method for preparing the modified MWW molecular sieve, which comprises: acid eluting the hydrogen-type MWW molecular sieve, adding a mercapto compound, oxidizing, and hydrothermally treating.
[0027] According to a preferred embodiment of the present invention, the preparation method comprises:
[0028] S1: A silicon source, an aluminum source, an alkali source, an organic structure directing agent, dicyclohexylamine and water are mixed to obtain a mixture, and then the mixture is crystallized, subjected to a first washing, a first drying, a first calcination, an ammonium exchange and a second calcination to obtain a hydrogen-type MWW molecular sieve.
[0029] S2: dispersing the hydrogen-type MWW molecular sieve in an acid solution to form a solution A; adding a thiol compound to the solution A, and then adding an oxidant to carry out an oxidation reaction to form a solution B;
[0030] S3: subjecting solution B to hydrothermal treatment, a second washing, and a second drying to obtain a modified MWW molecular sieve.
[0031] According to a preferred embodiment of the present invention, in step S1, the silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as OH -The molar ratio of SiO2:Al2O3:OH is 1:1. - : Organic structure directing agent: dicyclohexylamine: H2O=1: 0.015-0.050: 0.07-0.15: 0.20-0.30: 0.30-0.60: 14-30.
[0032] In the present invention, the type of silicon source is not particularly limited and can be a conventional choice in the art. According to a preferred embodiment of the present invention, the silicon source is silica sol.
[0033] In the present invention, the type of aluminum source is not particularly limited and can be a conventional choice in the art. According to a preferred embodiment of the present invention, the aluminum source is sodium aluminate.
[0034] In the present invention, the type of the alkali source is not particularly limited and can be a conventional choice in the art. According to a preferred embodiment of the present invention, the alkali source is sodium hydroxide.
[0035] According to a preferred embodiment of the present invention, the organic structure directing agent is hexamethyleneimine.
[0036] According to a preferred embodiment of the present invention, the crystallization condition of the mixture is 130-170° C. for 1-7 days.
[0037] In the present invention, the first washing method can be a conventional choice in the art, as long as the purpose of the present invention can be achieved.
[0038] In the present invention, the first drying condition can be a conventional choice in the art, as long as the purpose of the present invention can be achieved. The present invention takes drying in an oven at 100° C. overnight as an example to illustrate the advantages of the present invention.
[0039] In the present invention, the conditions for the first calcination and the second calcination can be conventionally selected in the art as long as the purpose of the present invention can be achieved. The first calcination and the second calcination of the present invention are both calcined in air at 550°C for 6 hours to illustrate the advantages of the present invention.
[0040] In the present invention, the ammonium exchange method is selected by conventional techniques in the art, as long as the purpose of the present invention can be achieved.
[0041] According to a preferred embodiment of the present invention, the acid solution in step S2 is at least one of hydrochloric acid, sulfuric acid and nitric acid, preferably hydrochloric acid.
[0042] According to a preferred embodiment of the present invention, the molar concentration of the acid solution in step S2 is 0.5-10 mol / L, preferably 0.8-4 mol / L.
[0043] According to a preferred embodiment of the present invention, the mass ratio of the hydrogen-type MWW molecular sieve to the acid solution in step S2 is 0.005-0.1, preferably 0.005-0.05.
[0044] According to a preferred embodiment of the present invention, the thiol compound in step S2 is selected from at least one of mercaptoethanol, thioglycolic acid, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, dimethylmercaptopropionic acid, methyl mercaptopropionate, 1,3-dimercaptopropane, and 2,3-dimercapto-1-propanol, and is preferably at least one of mercaptoethanol, thioglycolic acid, 3-mercaptopropyltrimethoxysilane, and 3-mercaptopropyltriethoxysilane.
[0045] In the present invention, the type of oxidant in step S2 is not particularly limited and can be a conventional choice in the art. According to a preferred embodiment of the present invention, the oxidant in step S2 is H2O2.
[0046] According to a preferred embodiment of the present invention, the mass ratio of the mercapto compound to the hydrogen-type MWW molecular sieve is 0.005-2.0, preferably 0.5-1.0.
[0047] According to a preferred embodiment of the present invention, the molar ratio of the thiol compound to the oxidant is 0.001-1.0, preferably 0.005-0.5.
[0048] According to a preferred embodiment of the present invention, the conditions of the oxidation reaction include: temperature of 5-40°C, preferably 10-25°C, and time of 3-24h, preferably 6-16h.
[0049] According to a preferred embodiment of the present invention, the conditions of the hydrothermal treatment in step S3 include: a temperature of 50-180° C., preferably 70-130° C.; and a time of 3-40 h, preferably 6-15 h.
[0050] In the present invention, the second washing method can be a conventional choice in the art, for example, washing the crystallized liquid with deionized water and ethanol for several times, for example, 2-5 times, until the upper clear liquid is neutral;
[0051] In the present invention, the second drying conditions can be conventionally selected in the art. According to a preferred embodiment of the present invention, the drying conditions include: a temperature of 30-120°C, preferably 50-100°C; and a time of 1-24h, preferably 5-15h.
[0052] The present invention provides an application of the modified MWW molecular sieve as an adsorbent and / or a catalyst for organic compound conversion, preferably an application in catalyzing biomass dehydration reaction and etherification reaction.
[0053] The molecular sieve catalyst with the characteristics of the present invention is used for biomass dehydration and etherification reactions, which can effectively promote the diffusion of biomass macromolecules and reduce the formation of carbon deposits. Sugar macromolecules react on the active sites on the outer surface of the catalyst and quickly desorb without overreacting. That is, the molecular sieve of the present invention has the advantages of high activity, good selectivity, good environmental protection and easy recovery when used for biomass dehydration and etherification reactions.
[0054] The invention provides a method for dehydrating or etherifying biomass, which comprises: mixing biomass, deionized water, an organic solvent and a catalyst, and then charging an inert gas, preferably nitrogen, into the mixed mixture to react and obtain a target product.
[0055] According to a preferred embodiment of the present invention, the organic solvent is at least one of toluene, cyclohexane, dichloromethane, tetrahydrofuran, acetone and methyl isobutyl ketone.
[0056] According to a preferred embodiment of the present invention, in the biomass dehydration reaction, the volume ratio of the organic solvent to deionized water is 4-20: 1, preferably 6-15: 1. The use of a higher organic solvent / water ratio can largely avoid the occurrence of side reactions.
[0057] According to a preferred embodiment of the present invention, in the biomass etherification reaction, the volume ratio of the organic solvent to deionized water is 1:4-20, preferably 1:6-15.
[0058] According to a preferred embodiment of the present invention, the mass ratio of the biomass to the catalyst is 1-50:1, preferably 1-20:1.
[0059] According to a preferred embodiment of the present invention, the mass ratio of the biomass to deionized water is 0.01-1:1, preferably 0.2-0.8:1.
[0060] According to a preferred embodiment of the present invention, the reaction conditions include: reaction temperature of 80-220° C., preferably 100-180° C.; reaction time of 10 min-20 h, preferably 10-200 min.
[0061] The present invention will be described in detail below by way of examples. However, the examples are only used to help understand the present invention and should not be regarded as specific limitations of the present invention. In the following examples, the raw materials are all commercially available.
[0062] In the present invention, the reaction product 5-hydroxymethylfurfural is analyzed qualitatively and quantitatively by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of the soluble carbohydrates in the product is analyzed by high performance liquid chromatography (HPLC). The gas chromatography-mass spectrometry instrument is Agilent 7890A of Agilent Corporation of the United States, the chromatographic column is HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph is Agilent 7890B, the detector is a hydrogen flame ionization detector (FID), and the chromatographic column is SE-54 capillary column (30m, 0.53mm). The high performance liquid chromatography adopts Agilent 1200 analysis, and the chromatographic column is SHODEX SC1011 sugar column (8×300mm).
[0063] In the present invention, the mass fraction of the S element of the catalyst is measured by an inductively coupled plasma atomic emission spectrometer (ICP), model Varian 725-ES, and a physical adsorption instrument model Micromeretic ASAP2020M, and the analysis sample is dissolved with hydrofluoric acid to obtain the content of the element. After obtaining the mass fraction of the S element, the -SO3H content is obtained by conversion.
[0064] In the present invention, the XRD measurement method of the catalyst is: using a Rigaku Ultima IV X-ray powder diffractometer from Japan to analyze the physical phase of the sample, and using a CuKα ray source. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.
[0065] In the present invention, the scanning electron microscope (SEM) photos of the catalyst were taken on a Hitachi S-4800II scanning electron microscope. The acceleration voltage of the instrument was 15 kV, and the samples were chromium-plated before analysis.
[0066] In the present invention, the pyridine adsorption infrared (py-FTIR) method is used to determine the type of catalyst acid, and the py-FTIR spectrum is obtained on a Nicolet Model 710 spectrometer. The specific operation steps are as follows: a. Sample preparation and pretreatment, about 15 mg of sample is pressed into a thin disc with a diameter of 13 mm and loaded into an infrared sample tank; then the sample is pretreated at 120° C. for 2 hours in a vacuum cell. The sample is scanned at 100° C. to obtain a background spectrum. b. After the sample tank is cooled to room temperature, pyridine is adsorbed for 10 minutes. Vacuum desorption is performed at 100° C. for 10 minutes, and the infrared absorption spectrum is scanned and recorded. The difference spectrum before and after pyridine adsorption is the obtained Py-FTIR spectrum.
[0067] In the present invention, the test instrument and test method for the average pore size, specific surface area and pore volume of the sample are: physical adsorption measurement is performed by nitrogen at -196°C using a 3H-2000PM2 physical adsorption instrument to analyze the pore structure characteristics of each adsorption material sample. The initial degassing condition is: degassing operation at 150°C for 6 hours. After measuring the adsorption isotherm of nitrogen on the sample, the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) method, and the pore volume and pore size distribution are calculated using the BJH (Barrett-Joyner-Halenda) method.
[0068] Fructose conversion rate (%) = (molar amount of fructose participating in the reaction) / (molar amount of fructose as the reaction substrate) × 100%.
[0069] The yield of the product 5-hydroxymethylfurfural (%) = (the molar amount of 5-hydroxymethylfurfural produced by the reaction) / (the molar amount of fructose reacted)×100%.
[0070] HMF conversion rate % = (molar amount of HMF participating in the reaction) / (molar amount of HMF as the reaction substrate) × 100%.
[0071] Yield of product EMF % = (molar amount of EMF generated by the reaction) / (molar amount of HMF reacted)×100%.
[0072] Example 1
[0073] Preparation of hydrogen-type MWW molecular sieve: Deionized water, sodium aluminate (containing 40.5% by weight of Al2O3 and 30.6% by weight of Na2O), sodium hydroxide, hexamethyleneimine, dicyclohexylamine, and silica sol (containing 40.0% by weight of SiO2) were mixed and stirred at room temperature for 3 hours to obtain a mixture. The final material ratio was calculated as follows in molar ratio:
[0074] SiO2 / Al2O3=30;
[0075] NaOH / SiO2=0.09;
[0076] Hexamethyleneimine / SiO2=0.2
[0077] Dicyclohexylamine / SiO2=0.50
[0078] H2O / SiO2=18
[0079] The mixture was placed in a stainless steel reactor and heated for crystallization at 150°C and 150 rpm for 4 days. After crystallization, the mixture was filtered, washed, dried overnight in an oven at 100°C, and calcined in air at 550°C for 6 hours. The sample obtained was a molecular sieve with MWW structure as determined by XRD. The SiO2 / Al2O3 molar ratio of the synthesized molecular sieve was 29.5 as measured by inductively coupled plasma atomic emission spectroscopy (ICP). The molecular sieve was subjected to ammonium ion exchange and calcined in air at 550°C for 6 hours to obtain a hydrogen-type SCM-1 molecular sieve.
[0080] The steps for preparing modified SCM-1 molecular sieve from hydrogen SCM-1 are as follows:
[0081] (1) Prepare a 2.0 M HCl solution, weigh 1 g of the hydrogen-type SCM-1 molecular sieve and disperse it in 100 g of hydrochloric acid. After stirring for 2 h, add 0.8 g of 3-mercaptopropyltrimethoxysilane dropwise. After continuing to stir for 20 min, add 1.5 g of hydrogen peroxide (30 wt %) dropwise, and then continue to stir at room temperature (25° C.) for 24 h.
[0082] (2) The stirred solution was placed in a hydrothermal reactor and reacted at 100°C for 12 hours.
[0083] (3) The crystallized liquid was washed with deionized water and ethanol several times until the upper clear liquid was neutral, and then dried at 80°C for 20 hours. Figure 1 As shown in the figure, the characteristic peaks of modified SCM-1 and hydrogen SCM-1 are the same, but the peak intensity is reduced. The value of external specific surface area / total specific surface area measured by BET is 0.35, and the N2- adsorption and desorption is shown in the figure. Figure 2 As shown. The S content was determined by ICP, and the SiO2 / SO3H molar ratio was calculated to be 43.2. The infrared spectrum of pyridine is shown Figure 3 As shown, The ratio is 2.6. SEM images are shown in Figure 5 As shown in (a), the crystal is in the form of a thin sheet with a crystal thickness of 6.3 nm.
[0084] Example 2
[0085] The difference from Example 1 is that the material ratio of SCM-1 synthesis is SiO2 / Al2O3=35, and the other steps remain the same to obtain a modified SCM-1 molecular sieve. Figure 1 Similar. The value of external specific surface area / total specific surface area measured by BET is 0.38. The molar ratio of SiO2 / SO3H is 45.8 as calculated by ICP determination of S content. The ratio is 2.7. SEM images and Figure 5 (a) is similar, the crystal thickness is 6.2 nm.
[0086] Example 3
[0087] The difference from Example 1 is that the hydrogen-type SCM-1 molecular sieve is weighed in 1.0M hydrochloric acid, and the other steps remain the same to obtain the modified SCM-1 molecular sieve. Figure 1 Similar. The value of external specific surface area / total specific surface area measured by BET is 0.36. The molar ratio of SiO2 / SO3H is 50.7 as calculated by ICP determination of S content. The ratio is 2.3. SEM images and Figure 5 (a) is similar, but the crystal thickness is 6.5 nm.
[0088] Example 4
[0089] The difference from Example 1 is that the hydrogen-type SCM-1 molecular sieve is weighed in 5.0M hydrochloric acid, and the other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.28. The molar ratio of SiO2 / SO3H is 58.5 as calculated by ICP determination of S content. Pyridine infrared measurement The ratio of XRD and Figure 1 Similar. SEM images and Figure 5 (a) is similar, the crystal thickness is 6.1 nm.
[0090] Example 5
[0091] The difference from Example 1 is that after the hydrogen-type SCM-1 molecular sieve is dispersed, 1.6 g of 3-mercaptopropyltrimethoxysilane is added dropwise thereto, and after stirring for 20 minutes, 3.0 g of hydrogen peroxide (30 wt%) is added dropwise. The other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.33. The molar ratio of SiO2 / SO3H is calculated by ICP determination of S content and is 40.3. Pyridine infrared measurement The ratio is 2.5. Figure 1 Similar. SEM images and Figure 5 (a) is similar, the crystal thickness is 6.9 nm.
[0092] Example 6
[0093] The difference from Example 1 is that after the hydrogen-type SCM-1 molecular sieve is dispersed, 0.4 g of 3-mercaptopropyltrimethoxysilane is added dropwise thereto, and after stirring for 20 minutes, 0.75 g of hydrogen peroxide (30 wt%) is added dropwise. The other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.34. The molar ratio of SiO2 / SO3H is calculated by ICP determination of S content and is 48.1. Pyridine infrared measurement The ratio of XRD and Figure 1 Similar. SEM images and Figure 5 (a) is similar, but the crystal thickness is 6.0 nm.
[0094] Example 7
[0095] The difference from Example 1 is that after the hydrogen-type SCM-1 molecular sieve is dispersed, 0.8 g of mercaptoethanol is added dropwise thereto, and after stirring for 20 minutes, 1.5 g of hydrogen peroxide (30 wt%) is added dropwise. The other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.35. The molar ratio of SiO2 / SO3H is 45.3 as calculated by ICP determination of S content. Pyridine infrared measurement The ratio is 2.4. Figure 1 Similar. SEM images and Figure 5 (a) is similar, the crystal thickness is 5.7 nm.
[0096] Example 8
[0097] The difference from Example 1 is that the hydrothermal temperature in the step of preparing the modified SCM-1 molecular sieve from H-SCM-1 is changed to 50°C, and the other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.31. The SiO2 / SO3H molar ratio is 60.8, which is calculated by ICP determination of S content. Pyridine infrared measurement The ratio is 1.8. Figure 1 Similar. SEM images and Figure 5 (a) is similar, the crystal thickness is 5.8 nm.
[0098] Example 9
[0099] The difference from Example 1 is that the hydrothermal temperature in the step of preparing the modified SCM-1 molecular sieve from hydrogen SCM-1 is changed to 120°C, and the other steps remain the same to obtain the modified SCM-1 molecular sieve. The value of the external specific surface area / total specific surface area measured by BET is 0.38. The SiO2 / SO3H molar ratio is 51.7, which is calculated by ICP determination of S content. Pyridine infrared measurement The ratio is 2.2. Figure 1 Similar. SEM images and Figure 5 (a) is similar, the crystal thickness is 7.2 nm.
[0100] Examples 10-18
[0101] With fructose as substrate, 0.2g of the modified SCM-1 in the above-mentioned Examples 1-9 (corresponding to Examples 10-18 in sequence), 0.4g of fructose, 18g of THF and 2g of deionized water were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 145°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 1.
[0102] Table 1
[0103] Fructose conversion rate (%) HMF yield (%) Example 10 99.9 86.9 Embodiment 11 99.9 85.8 Example 12 99.2 82.8 Embodiment 13 99.5 79.2 Embodiment 14 99.7 85.3 Embodiment 15 99.1 80.1 Example 16 99.2 83.7 Embodiment 17 99.0 75.8 Embodiment 18 99.3 83.5
[0104] Examples 19-23
[0105] With HMF and ethanol as reactants, tetrahydrofuran (THF) and deionized water as solvents, 0.2g of the modified SCM-1 in the above Examples 1-5 (corresponding to Examples 19-23 in sequence), 0.3g of HMF, 4g of THF, 15g of ethanol, and 1g of deionized water were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The heating jacket was heated to a preset temperature using a programmed temperature increase, and then stirred using a magnetic stirrer. The reaction was carried out at 125°C for 2.5h, and the reaction solution was analyzed to obtain the HMF conversion rate and the target product EMF yield, as shown in Table 2.
[0106] Table 2
[0107] HMF conversion rate (%) EMF yield (%) Embodiment 19 98.9 82.5 Embodiment 20 98.5 80.3 Embodiment 21 99.3 83.7 Embodiment 22 99.5 85.6 Embodiment 23 98.2 80.8
[0108] Comparative Example 1
[0109] Prepare 2.0M HCl, weigh 1g of the hydrogen-type SCM-1 molecular sieve prepared in the example and disperse it in 100g of hydrochloric acid, then put the stirred solution into a crystallization kettle and react at 100°C for 12h.
[0110] The crystallized liquid was washed with deionized water and ethanol several times until the supernatant was neutral, and then dried at 80°C for 20 hours to obtain HCl-washed hydrogen-type SCM-1. Figure 1 As shown, the value of the external specific surface area / total specific surface area measured by BET is 0.37, and the pyridine infrared image is shown in Figure 3 , measured The ratio is 1.25.
[0111] With fructose as substrate, tetrahydrofuran (THF) and deionized water as solvent, 0.2g of the above hydrogen SCM-1, 0.4g of fructose, 18g of THF and 2g of deionized water were added into a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 145°C for 30min, and the reaction solution was analyzed to obtain a fructose conversion rate of 99.3% and a target product 5-hydroxymethylfurfural (HMF) yield of 63.7%.
[0112] Comparative Example 2
[0113] With HMF and ethanol as reactants, tetrahydrofuran (THF) and deionized water as solvents, 0.2g of the hydrogen-type SCM-1 in the above comparative example 1, 0.3g of HMF, 4g of THF, 15g of ethanol, and 1g of deionized water were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 125°C for 2.5h, and the reaction solution was analyzed to obtain a HMF conversion rate of 99.5% and a target product EMF yield of 70.1%.
[0114] Comparative Example 3
[0115] The MCM-22 molecular sieve raw powder synthesized according to the preparation method described in the literature [Chinese Journal of Catalysis 41(2020)1062-1066] was calcined to remove the structure directing agent, and then ion exchange and calcination were performed to obtain hydrogen-type MCM-22.
[0116] The steps for preparing modified MCM-22 molecular sieve from hydrogen-type MCM-22 are as follows:
[0117] (1) Prepare 2.0 M HCl, weigh 1 g of the hydrogen-type MCM-22 molecular sieve and disperse it in 100 g of hydrochloric acid. After stirring for 2 h, add 0.8 g of 3-mercaptopropyltrimethoxysilane dropwise. After continuing to stir for 20 min, add 1.5 g of hydrogen peroxide (30 wt%) dropwise, and then continue to stir at room temperature for 24 h.
[0118] (2) The stirred solution was placed in a crystallization reactor and reacted at 100°C for 12 hours.
[0119] (3) The crystallized liquid was washed with deionized water and ethanol several times until the upper clear liquid was neutral, and then dried at 80°C for 20 hours. Figure 5As shown in (b), the crystals are in the form of thin sheets, and their thickness is greater than that of hydrogen-type SCM-1. The value of the external specific surface area / total specific surface area measured by BET is 0.10. The molar ratio of SiO2 / SO3H is 205 as calculated by ICP determination of S content. Figure 4 It can be seen that the -OH on the surface of hydrogen-type SCM-1 is higher than that of MCM-22, so the surface of hydrogen-type SCM-1 can be connected with more -SH, and then after oxidation, there will be a higher content of -SO3H.
[0120] With fructose as substrate, tetrahydrofuran (THF) and deionized water as solvent, 0.2g of the modified MCM-22, 0.4g of fructose, 18g of THF and 2g of deionized water were added into a stirred autoclave. 0.5MPa of nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 145°C for 30min, and the reaction solution was analyzed to obtain a fructose conversion rate of 99.5% and a target product 5-hydroxymethylfurfural (HMF) yield of 55.7%.
[0121] Comparative Example 4
[0122] With HMF and ethanol as reactants, tetrahydrofuran (THF) and deionized water as solvents, 0.2g of the modified MCM-22 in the above comparative example 3, 0.3g of HMF, 4g of THF, 15g of ethanol, and 1g of deionized water were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 125°C for 2.5h, and the reaction solution was analyzed to obtain an HMF conversion rate of 98.3% and a target product EMF yield of 65.8%.
[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A modified MWW molecular sieve, characterized in that: The modified MWW molecular sieve has a schematic chemical composition as shown in the formula "mSiO2·nAl2O3·pSO3H", wherein 20≤m / n≤66, 25≤m / p≤150.
2. The modified MWW molecular sieve according to claim 1, wherein The schematic chemical composition of the modified MWW molecular sieve is 22≤m / n≤60, 26≤m / p≤130, preferably 25≤m / n≤55, 28≤m / p≤100.
3. The modified MWW molecular sieve according to claim 1 or 2, wherein: The modified MWW molecular sieve The acid / Lewis acid ratio is 1.5-5.0, preferably 1.9-4.
0.
4. The modified MWW molecular sieve according to any one of claims 1 to 3, wherein: The external specific surface area / total specific surface area of the modified MWW molecular sieve is 0.2-0.9, preferably 0.3-0.
7.
5. The modified MWW molecular sieve according to any one of claims 1 to 4, wherein: The modified MWW molecular sieve has a nano-sheet morphology, and the crystal thickness is 5-15 nm, preferably 5-12 nm.
6. A method for preparing a modified MWW molecular sieve, characterized in that: The preparation method comprises: acid elution of hydrogen-type MWW molecular sieve, addition of mercapto compounds, oxidation, and hydrothermal treatment; Preferably, the preparation method comprises: S1: A silicon source, an aluminum source, an alkali source, an organic structure directing agent, dicyclohexylamine and water are mixed to obtain a mixture, and then the mixture is crystallized, subjected to a first washing, a first drying, a first calcination, an ammonium exchange and a second calcination to obtain a hydrogen-type MWW molecular sieve. S2: dispersing the hydrogen-type MWW molecular sieve in an acid solution to form a solution A; adding a thiol compound to the solution A, and then adding an oxidant to carry out an oxidation reaction to form a solution B; S3: subjecting solution B to hydrothermal treatment, a second washing, and a second drying to obtain a modified MWW molecular sieve.
7. The preparation method according to claim 6, wherein: In step S1, The silicon source is calculated as SiO2, the aluminum source is calculated as Al2O3, the alkali source is calculated as OH-, the organic structure directing agent, dicyclohexylamine and water, and the molar ratio is SiO2:Al2O3:OH-:organic structure directing agent:dicyclohexylamine:H2O=1:0.015-0.050:0.07-0.15:0.20-0.30:0.30-0.60:14-30; and / or The organic structure directing agent is hexamethyleneimine; and / or The crystallization conditions of the mixture are 130-170° C. for 1-7 days.
8. The preparation method according to claim 6 or 7, wherein: In step S2, The acid solution is at least one of hydrochloric acid, sulfuric acid and nitric acid, preferably hydrochloric acid; and / or The molar concentration of the acid solution is 0.5-10 mol / L, preferably 0.8-4 mol / L; and / or The mass ratio of the hydrogen-type MWW molecular sieve to the acid solution is 0.005-0.1, preferably 0.005-0.05; and / or The mercapto compound is selected from at least one of mercaptoethanol, mercaptoacetic acid, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, dimethylmercaptopropionic acid, methyl mercaptopropionate, 1,3-dimercaptopropane, and 2,3-dimercapto-1-propanol, preferably at least one of mercaptoethanol, mercaptoacetic acid, 3-mercaptopropyltrimethoxysilane, and 3-mercaptopropyltriethoxysilane; and / or The oxidant is H2O2; and / or The mass ratio of the mercapto compound to the hydrogen-type MWW molecular sieve is 0.005-2.0, preferably 0.5-1.0; and / or The molar ratio of the mercapto compound to the oxidant is 0.001-1.0, preferably 0.005-0.5; and / or The conditions of the oxidation reaction include: temperature of 5-40°C, preferably 10-25°C, and time of 3-24h, preferably 6-16h.
9. The preparation method according to any one of claims 6 to 8, wherein: In step S3, the conditions of the hydrothermal treatment include: temperature of 50-180° C., preferably 70-130° C.; time of 3-40 h, preferably 6-15 h.
10. Use of the modified MWW molecular sieve according to any one of claims 1 to 5 and / or the modified MWW molecular sieve prepared by the preparation method according to any one of claims 6 to 9 as an adsorbent and / or a catalyst for conversion of organic compounds, preferably in catalyzing biomass dehydration reactions and etherification reactions.
Citation Information
Patent Citations
Solid acid catalyst for 5-hydroxymethyl furfural synthesis and preparation method thereof
CN103028424A
A molecular sieve, its manufacturing method and its application
CN104511271B
Crystalline aluminosilicate PSH-3 and its process of preparation
US4439409A